(NoLXGA bERGGOLXC(B. (NsOBRANIE SO^INENIJ W TREH TOMAH (B/ s - (NbERGGOLXC(B, (NoLXGAs ((NlENINGRAD(B: s (NhUDOVESTWENNAQ LITERATURAs)
(NoLXGA bERGGOLXC (B(1910 - 1975) - (NTONKIJ LIRIK(B, (NPO\T GORQ^EGO GRAVDANSKOGO TEMPERAMENTA(B, (NMASTER HUDOVESTWENNOJ PROZY(B, (NPUBLICIST I DRAMATURG(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs; (NpXESYs; (NpROZAs